The influence of Sm-153 therapy on bone marrow function - Małkowski, Bogdan; Maruszak, Marta; Dudek, Anna; Wędrowski, Mateusz; Szefer, Jarosław (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: Studies about possible risks connected with β-emitterradiotherapy concentrate mainly on potential myelotoxicity. Results of previously published analysis based on white blood cells (WBC) and platelet (PLT) counts – before and after radionuclide treatment – are quite varied. The aim of our study was to present the greatest possible impact of Samarium-153 on bone marrow function in clinical practice. Material and methods: The study included the blood test results of 175 patients with bone metastases treated with Sm-153 in the years 2012–2014. We compared levels of WBC, PLT, red blood cells (RBC), and haemoglobin (HGB) from two blood tests – one performed directly before the therapy and the other 2–6 weeks after isotope injection. Results and conclusions : The study showed decreased mean level of WBC in a control test performed after therapy in comparison to output results at about 27.1%. In our study 1.1% of patients developed the third-grade toxicity in CTCAE (Common Terminology Criteria for Adverse Events). Mean decrease of PLT was about 18%. Three patients (1.7% of all) result qualified as third-grade toxicity in a control test, one as fourth-grade. Analysis of RBC level showed 5.7% reduction of output values. The same calculation was seen for HGB – 5.1%. The greatest but acceptable decrease in haematological parameters was observed in WBC and PLT. Analysis of changes in WBC and PLT level showed them to be similar or smaller than was proven in previously published studies.